Academic performance, publishing and peer review: peering into the twilight zone. Issue 1 (19th January 2015) - Guthrie, James; Parker, Lee D; Dumay, John
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a critique of published research access and peer review, considering their impacts on accounting scholarship. Design/methodology/approach – The paper is based on literature and publishing document review, experiential reflections and argument. Findings – The authors reveal changes in publishing formats and accessibility, the challenges of managing research quality and significance and the challenges of avoiding constraint and foreclosure of significant new knowledge and its effective dissemination. Research limitations/implications – This paper discusses the research and publishing community's opening to new, flexible opportunities for knowledge creation and dissemination. Originality/value – The discussion challenges the status quo of traditional academic journal publication and points to an innovative future.